Chemical attributes of soil fertirrigated with biodigester effluent of swine origin - Coletto, Arthur Floresta; de Almeida, Risely Ferraz [UNESP]; Mikhael, Joseph Elias Rodrigues; Wendling, Beno; Camargo, Reginaldo (My University, 2015)
Swine production is a significant and growing part of Brazilian agriculture. Our objective was to determine nutrient availability in the soil after swine waste applications to pastureland and eucalyptus forestland and then compare these levels to those in the Cerrado (the Brazilian savannah). We concluded that applications of swine waste increased macro/micronutrient availability. Applications of swine waste were associated with higher concentrations of aluminum (Al+3), hydrogen and aluminum (Al+H), total organic carbon and microbial biomass carbon in the Cerrado and higher nutrient concentrations in pastures and eucalyptus stands. The topography and seepage rates should be considered when using pig manure as a soil fertilizer. Applications of pig manure increase macro and micronutrient availability in the soil. Applications in the Cerrado are related to higher concentrations of Al, Al+H, total organic carbon and soil microbial biomass, whereas applications to pasture and Eucalyptus sites lead to higher nutrient concentrations. None of the soil-use types examined in the study have characteristics similar to natural Cerrado. Pasture 1 was the most dissimilar to Cerrado, followed by Pasture 3, 4 and 2 and Eucalyptus.
Keywords: Soil fertility; Swine production; Wastewater